Pathological changes induced by avian encephalomyelitis virus in developing quail (coturnix coturnix japonica) embryos - Özer, Harun; Eröksüz, Hatice; Eröksüz, Yesari; Gülcu, Basri; Muz, Adile; Yilmaz, Fethi (Scientific and Technical Research Council of Turkey, 1996)
A 0.1 ml viral suspension of Avian Encephalomyelitis Virus. Van Roekel strain - AEV - VR (EIDS - 10-3) was inoculated into 7- day - old embriyonated quail eggs via yolk sac route to asses and demonstrate morphologic changes caused by the virus. Macroscopic and microscopic changes were appeared from 4 to 11 day of postinoculation. Immobility of the whole body, dwarfism and edema in the brain were the main macroscopic findings observed. Vascular proliferation, edema, mild gliosis, neuronal necrosis in the central nervous system, demyelination, gliosis and neuronal necrosis in medulla spinalis, ganglionitis in the spinal ganglions, degeneration, necrosis and dystrophy in the skelatal muscles were detected microscopically. Hatchability of infected embryos compared to uninfected group was much lower; 10.34%, 92.3% respectively. Although macroscopic changes in the quail embryos were similar to chicken embryo, some of the other characteristic lesions for the chicken embryo such as retracted toes, shrunken or crooked in configuration were not observed.
Avian Encaphalomyelitis Virusu ile Enfekte Edilmiş Bildircin (Coturnix coturnix japonica) Embriyolarinda Patolojik Bulgular
Keywords: Avian Encephalomyelitis; Experimental infection; Pathological findings; Quail embryo